Pengembangan Mesin Pengurai Serat Tandan Kosong Kelapa Sawit (TKKS) untuk Menghasilkan Serat Mekanis - Junaidi Junaidi; Anwar Kasim; Ardinal Ardinal (Jurnal Litbang Industri, 2016)
The purpose of this research was to design shredded oil palm empty fruit bunch (EFB) fiber extractor machine, to conduct technical evaluation on the machine performance, and to conduct fiber chemical analysis. This prototype is expected to increase added value on EFB waste as it is not maximally utilized. The machine must be both technically and economically feasible to be applied in particle board industry to produce oil palm empty fruit bunch fiber. Based on its design, the machine has ± 200 kg/hours capacity and 5 HP motor. The evaluation of machine performance on 600 RPM and 900 RPM rotations resulted on similar numbers of fiber and mixed fiber percentage. From 10 shredded EFB extracted, 7.6 kg (76%) clean fiber, 2.05 kg (20%) mixed fiber, and 1.35 kg ash were obtained. Three times extracting process on 600 RPM rotation resulted on fiber percentage based on its length as follows: 4.6% long fiber (>10 cm), 32.3% medium fiber (5-10 cm), and 61.4% short fiber (2-4 cm). Meanwhile, the percentages on 900 RPM rotation were 0% of long fiber, 22.37% of medium fiber, and short fiber of 77.3%. There were five types of composition of extracted fiber level; 1) clean fiber on 600 RPM, 2) clean fiber on 900 RPM, 3) mixed fiber (medium fiber 2-3 cm + petal), 4) mixed fiber (short fiber <2 cm + petal), 5) mixed fiber (soft fiber + pollens). The result of chemical analysis showed that those five types of fibers contained 9.3% water, 5.6% extractive, 1.4% fat, 33.1% lignin, 58.33% holocellulose, and 39.2% cellulose contents. Finally the analysis showed that it had a similar chemical composition compared to the fibers of softwood and Red Meranti wood.ABSTRAKPengembangan mesin pengurai serat tandan kosong kelapa sawit dilakukan untuk menghasilkan serat mekanis sebagai penguat papan partikel. Didalam penelitian ini dilakukan perancangan mesin, pembuatan mesin dan evaluasi teknis kinerja mesin. Evaluasi teknis dilakukan pada putaran 600 rpm dan 900 rpm dengan masing-masing putaran 2 kali penguraian, dan masing-masing penguraian 3 ulangan. Dari hasil rancangan mesin didapatkan kapasitas mesin ± 200 kg/jam dan daya penggerak  5 HP. Hasil evaluasi teknis kinerja mesin didapatkan persentase serat dan serat campuran pada putaran 900 rpm pada pengujian 1 dan 2 tidak berbeda jauh dengan pengujian pada putaran 600 rpm. Dari 10 kg TKKS cacahan masing-masing putaran, didapatkan rata-rata serat bersih  82%, serat campuran 14%, dan 4% menjadi debu. Dari hasil penguraian pada putaran 600 rpm dan 900 rpm didapatkan 5 macam komposisi tingkatan serat yaitu, a) serat bersih 600 rpm, b) serat bersih 900 rpm, c) serat campuran (2-3 cm+kelopak), d) serat campuran (<2 cm + kelopak), e) serat campuran (serat halus + serbuk). Hasil analisis kimia ke lima serat tersebut yaitu,  rata-rata kadar air serat 9,3%, kadar ekstraktif 5,6%, kadar lemak 1,4%, kadar lignin 33,1%, kadar holoselulosa 58,33%, dan selulosa 39,2%. Dibandingkan dengan serat kayu daun jarum dan kayu meranti merah, kandungan kimia serat tersebut hampir sama atau tidak berbeda jauh.